Teaching The Module "Pkt-2 Machine" On The Basis Of Interactive Methods (Global Scientific Review, 2023)
This article considers questions of scientifical-pedagogical foundation of modular yeducation, its application and yefficiency, also organizing and providing classes according to the module “General structure of PKT-2”.